Design of block copolymer micelles via crystallization. (7th April 2015) - Crassous, Jérôme J.; Schurtenberger, Peter; Ballauff, Matthias; Mihut, Adriana M.
Abstract: This Feature Article provides an overview of the progress made over the last few years in the design of diblock copolymer micelles based on crystallization - driven self-assembly (CDSA) towards the development of novel and fascinating morphologies with crystalline-cores. Here, we describe the different approaches employed in order to engineer a large variety of semicrystalline micellar architectures. We highlight kinetic strategies that have been employed to direct morphological transitions, which can then be further tuned thus increasing the range of possible micellar structures. We then emphasize the development of complex hybrid assemblies generated by taking advantage of the self-assembly process of crystalline-corona di-BCP micelles with colloidal particles. Each section introduces and emphasizes the potential applications of this class of nanomaterials. Graphical abstract: Highlights: How can we design diblock copolymer micelles via a controlled crystallization process. Which are the relevant parameters that can strongly influence their morphological development. How can we develop hybrid assemblies through controlled crystallization processes.